The Beginnings of Modern Research on Propolis in Poland. (23rd June 2013) - Kuropatnicki, Andrzej K.; Szliszka, Ewelina; Kłósek, Małgorzata; Król, Wojciech
Abstract : Propolis studies in Poland were initiated by Professor Stan Scheller in the 1960s. It was a team of Polish researchers who developed a method of introducing hydrophobic ethanol extracts of propolis (EEP) into aqueous solutions, which enabled the study of their biological properties. The studies performed in Poland showed that EEP possesses antioxidant, radioprotective, and immunostimulating properties. It was possible to demonstrate antibacterial activity of propolis on Gram-positive bacteria, virulent Mycobacterium tuberculosis, and protozoa as well as stimulating activity of aqueous extracts of propolis on proliferation of cells in vitro . Polish investigators showed that propolis stimulates regeneration of tissue, acts as antioxidant and radioprotector, has strong immunostimulative properties, affects animals' life span by extending it, and improves intellectual and life functions of the elderly.